Wildland-Urban Interface: Key Issues - Leslie Annie Hermansen-Baez; Jennifer Seitz; Martha C. Monroe (EDIS)
A result of the influx of new residents to the South is an expansion of urban areas into forests and other natural areas, creating areas referred to as the wildland-urban interface. Interface issues of most concern vary from state to state, but some key issues are consistent across the South. the US Forest Service conducted a series of focus groups in 2000. Key issues gleaned from those focus groups and other related sources are described in this 5-page fact sheet written by L. Annie Hermansen-Baez, Jennifer Seitz, and Martha C. Monroe, and published by the UF Department of School of Forest Resources and Conservation, February 2013.